Sensory evaluation of upland rice varieties with farmers: A case study - Singh, R.K.; Prasad, Kameshwari; Mandal, Nimai Prasas; Singh, Rama Kant; Courtois, Brigitte; Singh, Virendra Pal; Paris, T.R. (CGIAR System-wide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovations, 2001)
As part of a participatory plant-breeding project with methodological objectives lo improve rainfed rice in eastern India, an evaluation of sensory characteristics was conducted with farmers in a village of Bihar. Twenty-four farmers (12 women and 12 men) evaluated 15 upland rice varieties as raw rice and parboiled rice for milled and cooked rice appearance, color, odor, texture, stickiness, taste, and overall acceptability. The rice samples were milled and cooked by the women farmers following their ordinary practices, one variety recorded good result with both raw and parboiled modes of preparation, the preferences of women and men farmers did not differ significantly. The rankings based on preferences were compared with the rankings of the varieties for various physico-chemical characteristics measured in the laboratory, most correlations were not significant, indicating that, for the set of tested varieties, these parameters were poor predictors of farmers' preferences. the rankings based on preferences were compared with fanners' field rankings, and the correlation was positive for raw rice and negative for parboiled rice. Fanners' trade-off between field performance and grain quality is therefore important to asses for at least parboiled rice. The results of this first sensory evaluation experiment will be used to simplify Ihe methodology and to improve varietal evaluation in the formal breeding process.